Covid-19 and international business : change of era - Marinov, Marin; Marinova, Svetla Trifonova (New York: Routledge, 2021)
"The Covid-19 pandemic has induced a crisis grasping the world abruptly, simultaneously, and swiftly. As a critical juncture, it ignited a change of era for international business. This book illustrates how governments have dealt with the pandemic and the consequent impacts on international business. It also explores the disrupted operations and responses of businesses as their worldwide interconnectivity has been seriously threatened. The book discourses multidirectional aspects of the effects of Covid-19 on international business, ranging from the juxtaposing forces disrupting globalization and installing a change of era through decoupling of technological, production and knowledge flows to its stimulating aspects to the strategic response on business, industry and state level. The book contains thirty chapters that offer a multidimensional interpretation of impacts of Covid-19 on international business theory and practice. Employing the latest state of knowledge on the topic, the book is aimed at international business audience - scholars, students and managers who need to understand better the nature, scope and scale of the impacts of the pandemic on international business"--
Includes bibliographical references and index.
Keywords: International trade; International business enterprises; COVID-19 (Disease)